Evaluasi Pelaksanaan Sistem Kewaspadaan Dini Dan Respon (Skdr) Sebagai Upaya Deteksi Dini Kejadian Luar Biasa (KLB) - Rifai, Ahmad; Anggini.B, Wira (Jurnal Kesehatan Nusantara (JKN), 2025)
The Early Warning and Response System (SKDR) is a system that functions in detecting the threat of indications of infectious disease outbreaks reported weekly on a computer-based basis, which can display alerts or early warning signals of an increase in disease cases exceeding the threshold value in an area. The purpose of this study was to determine the Evaluation of the Implementation of the Early Vigilance and Response System as an effort to early detection of outbreak (KLB) at the Lembang Health Center, this research can be used as a source of information to understand and analyze the Early warnings and Response System (SKDR), the type of research used in this study is descriptive with a qualitative research design, researchers use triagulation collection techniques or a combination of observation, interview and documentation. The results of data analysis from this study are an evaluation of the implementation of input indicators, the workforce is sufficient as evidenced by having conducted training 3 times, the funds are still not enough if adjusted to the existing alerts, the supporting facilities are adequate but the problem is that the refrigerator as one of the supporting sample storage is still not optimal, in the process indicators have been carried out optimally even though data collection from clinics is still a challenge, while the output indicators are very good with the accuracy and completeness of the data reaching 100%